IDENTIFY ABUSE STAY PERMIT BY FOREIGNERS IN INDONESIA - Annisa Niazela; Anita Herlina (Journal of Law and Border Protection, 2020)
Abuse is applying something that is not what it should be. Foreigners often try this matter by violating the provisions of the time limit for a stay permit (overstay). Immigration law enforcement in this matter must really be enforced so that this matter does not happen again. Based on Law No. 6 of 2011 on Immigration, to prevent abuse of residence permits and law enforcement against foreigners who violate the requirements of a residence permit, monitoring of administrative completeness is intended for foreign citizens who enter Indonesian territory and take administrative actions. as well as legal remedies through a legal panel process. In this matter, it means to improve Human Resources (HR) in all aspects of immigration